Relative Deprivation and Prosocial Tendencies in Chinese Migrant Children: Testing an Integrated Model of Perceived Social Support and Group Identity - Xiong, Meng; Xiao, Lei; Ye, Yiduo (Frontiers in Psychology, 2021)
As a particularly vulnerable group, children from rural areas in China whose families migrate to urban areas often encounter social exclusion, prejudice, and discrimination as they adjust to city life. Hence, migrant children may experience a sense of relative deprivation when they feel they are treated unjustly when compared to their urban counterparts. Although previous research has demonstrated that relative deprivation is a risk factor for prosocial tendencies, this association has not yet been examined in the population of migrant children in China. Further, few studies have revealed the mediating and moderating mechanisms between relative deprivation and prosocial tendencies. Therefore, this study constructed an integrated model examining the possible mediating role of perceived social support and moderating role of in-group identity on the association between relative deprivation and prosocial tendencies. A large sample of 1,630 Chinese rural-to-urban migrant children (845 girls; Mage = 12.30, SD = 1.74) completed a battery of self-report questionnaires regarding relative deprivation, prosocial tendencies, perceived social support, in-group identity, and demographic variables. The results indicated that relative deprivation was negatively correlated with migrant children's prosocial tendencies and this connection was partially mediated by perceived social support. Moderated mediation analysis further indicated that in-group identity moderated the effect of perceived social support on prosocial tendencies, with a high level of in-group identity strengthening the positive association between perceived social support and prosocial tendencies. Parents, educators, and other members of society concerned about migrant children's psychosocial adaptation should provide adequate social support resources and help them foster positive in-group identity to migrant populations to mitigate the adverse effects of relative deprivation and promote their prosocial tendencies.